Do Stories About Lying and Honesty Reduce Lie-Telling Behaviors in Children? - Muhammed Sukru Aydin (Studia Psychologica)
Since lying is a negative phenomenon, it has inspired theoretical and applied research on how to reduce such behaviors. Therefore, in the current study, we aimed to examine whether children’s lie-telling behaviors are affected by honesty- and lie-themed stories using an experimental design. A total of 176 children (85 girls), aged 4 to 5 years, were included in the study. We randomly assigned participants to three different experimental groups in which they were told the importance of honesty (the honesty story), the short-term negative consequences of lying (Pinocchio), and the fact that lying is a terrible behavior with important consequences (The Boy Who Cried Wolf). No moral story was told to the children in the control group. Then, we utilized a “temptation resistance task” to measure the lie-telling behaviors of the children in the control and experimental groups. The results showed that the children in the control group lied more often than the children in all the experimental groups. The analyses conducted to ascertain the differences among the groups also revealed that children who listened to Pinocchio used significantly fewer lie-telling behaviors compared to the children who listened to the honesty story and the children in the control group.